Association of Low Ficolin–Lectin Pathway Parameters with Cardiac Syndrome X. (September 2016) - Horváth, Z.; Csuka, D.; Vargova, K.; Leé, S.; Varga, L.; Garred, P.; Préda, I.; Zsámboki, E. T.; Prohászka, Z.; Kiss, R. G.
Abstract: In patients with typical angina pectoris, inducible myocardial ischaemia and macroscopically normal coronaries (cardiac syndrome X (CSX)), a significantly elevated plasma level of terminal complement complex (TCC), the common end product of complement activation, has been observed without accompanying activation of the classical or the alternative pathways. Therefore, our aim was to clarify the role of the ficolin–lectin pathway in CSX. Eighteen patients with CSX, 37 stable angina patients with significant coronary stenosis (CHD) and 54 healthy volunteers (HC) were enrolled. Serum levels of ficolin‐2 and ficolin‐3, ficolin‐3/MASP‐2 complex and ficolin‐3‐mediated TCC deposition (FCN3‐TCC) were determined. Plasma level of TCC was significantly higher in the CSX than in the HC or CHD group (5.45 versus 1.30 versus 2.04 AU/ml, P  < 0.001). Serum levels of ficolin‐2 and ficolin‐3 were significantly lower in the CSX compared to the HC or CHD group (3.60 versus 5.80 or 5.20  μ g/ml, P  < 0.05; 17.80 versus 24.10 or 26.80  μ g/ml, P  < 0.05). The ficolin‐3/MASP‐2 complex was significantly lower in the CSX group compared to the HC group (92.90 versus 144.90 AU/ml, P  = 0.006). FCN3‐TCC deposition was significantly lower in the CSX group compared to the HC and CHD groups (67.8% versus 143.3% or 159.7%, P  < 0.05). In the CSX group, a significant correlation was found between TCC and FCN3‐TCC level ( r  = 0.507, P  = 0.032) and between ficolin‐3/MASP‐2 complex level and FCN3‐TCC deposition ( r  = 0.651, P  = 0.003). In conclusion, in patients with typical angina and myocardial ischaemia despite macroscopically normal coronary arteries, low levels of several lectin pathway parameters were observed, indicating complement activation and consumption. Complement activation through the ficolin–lectin pathway might play a role in the complex pathomechanism of CSX.